MEDIASI PROFITABILITAS PADA PENGARUH STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Saniyyatuz Zulfa (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2021)
Â In general, this study aims to test the mediation of profitability on the influence of capital structure and company growth on the value of telecommunications companies. The sample of the research object is used 30 from the 5 annual report periods of 6 telecommunications companies listed on the Indonesia stock exchange. The results obtained are then processed using path analysis method with the help of SPSS and SmartPLS. The results of this study indicate that the R-square value is 0.2803 and the R-square value of the profitability variable is 0.008 which indicates that construct variability especially profitability cannot be explained by the variability of the capital structure construct and growth because it is only 0.08% . From the results of hypothesis testing it was found that profitability cannot mediate the effect of capital structure and company growth on the value of telecommunications companies. Direct influence is obtained only on the relationship of capital structure and profitability to the value of the company, besides that the hypothesis of direct influence is rejected.Â Keywords: Mediation, Profitability, Capital Structure, Company Growth, Corporate Value, Telecommunications Company, Indonesia Stock Exchange